ENERGY INFRASTRUCTURE AND THE DEVELOPMENT OF TOURISM IN POSAVJE - Veljković, Božidar; Colarič Jakše, Lea Marija (Journal of Energy Technology, 2024)
One strategy of Slovenian tourism development is based on the development of the Posavje region. Our aim was to discover how new energy infrastructure in Posavje will add to the development of new tourism products. We conducted the study in the Posavje using correspondence analysis. The study of the attitudes of the local residents toward tourism products shows that products are evenly distributed in the region, and that there are new opportunities for the development of new tourism products associated with water spaces. These new products are the basis for the development more integrated and varied tourism in the Posavje region.